Relationship Age with Anxiety In Children Undergoing Hospitalization at General Hospital In Muna Regency - Dian RL; Wahidah Rohmawati; Umar Wiranto; Bety Anisa Wulandari (Politeknik Karya Persada Muna, 2022)
Baground: Childhood is the most vulnerable time for anxiety syndrome since anxiety syndrome will continue to adolescent, and 15-20% can cause trauma, decreased school performance, turnover of mental health disorders such as depression and early treatment due to psychiatric disorders. Method: This research is an analytical observational study with a cross sectional approach and this research was conducted in October 2021 with a total sample 0f 173 using purposive sampling technique. Result: the result of the analysis showed that 51 respondents (21,9%) experienced moderate anxiety, age 2-5 years anda 30 respondent (17,3%) experienced mild anxiety and the chi-square test showed that the p value from a = 0,05 which means that there is a significant relationship between the age of the child and anxiety.Conclusion: the result of the bivariate test showed that there was a relationship between the child’s age and anxiety in children undergoing hospitalization.Keywords: Hospitalization, anxiety, age